PROFILE OF STUDENTS' METACOGNITIVE SKILLS IN SOLVING MATH PROBLEMS IN TERMS OF MATHEMATICAL ABILITY - Restini, I Luh; Pathuddin, pathuddin; Bakri, bakri; Sukayasa, sukayasa (JME (Journal of Mathematics Education), 2023)
Understanding students' metacognitive skills in solving math problems concerning their mathematical abilities is crucial for identifying the cognitive processes involved in problem-solving. This study investigates the metacognitive skills of SMPN 3 Palu students with varying mathematical abilities in problem-solving. It focuses on students in class VIIJ during the 2022/2023 academic year, individually analyzing one high-ability and one low-ability student. The research, descriptive in nature, employs qualitative methods using written assignments and interviews for data collection. This study's analysis involved condensing data, presenting findings, and drawing conclusions. The findings reveal distinct approaches between high and low mathematical ability subjects. High-ability students consistently apply all three metacognitive skills (planning, monitoring, and assessment) across each problem-solving stage. Conversely, low-ability students demonstrate a limited use of metacognitive skills. While they employ planning at each stage, during implementation and result review, they primarily engage in planning and monitoring, neglecting assessment. Ultimately, it underscores the critical role of metacognitive skills in mathematical problem-solving, highlighting differences in their application between students of varying mathematical abilities.Â Â